Legislative significance of custom in developing local family fiqh: an analysis of its conceptual framework - Haneef, Sayed Sikandar Shah; Fatah Yasin, Raudlotul Firdaus; Ijaz, Rabia (Islamic Book Trust, 2021)
Shari`ah as a comprehensive divine code of conduct aims at guiding and inspiring human beings on top of regulating their personal and social conduct, both vertically and horizontally. In the family sphere, the ShariÑah while prescribing some fundamental laws in order to regulate interfamilial relationships leaves sufficient rooms for the absorption of social practices and norms (customs) which facilitate the realization of its ethical-religious and socio-cultural vision of establishing strong families and the nurturing of harmonious individuals and communities. It is also rational as Evan (2014) asserts: “Custom is held to be a factual assertion of need and values of people of a given community at any point in time. Common human social order dictates presumably that certain practices which had developed become instrument of regulating everyday relationships among people. Slowly and irresistibly, they become norms of that particular community. Thus, ‘the way things have always been done becomes the way things must be done”.